Implementasi Manajemen Kinerja Berbasis Islam dalam Meningkatkan Mutu Pendidikan di MIS Cendikia Insani Al Washliyah - Afrida Yani; Ahmad Ridwan; Azmi Yuliana (Fakultas Agama Islam Universitas Al Washliyah, 2025)
The quality of education, particularly in Islamic educational institutions in Indonesia, still faces challenges such as inefficient management and suboptimal integration of religious values. This study aims to analyze the implementation of Islamic-based performance management at MIS Cendekia Insani Al Washliyah, identifying its supporting and hindering factors. Employing a qualitative descriptive approach with a case study method, the research was conducted over six months. Data collection involved participant observation, semi-structured interviews, and documentation with the principal, teachers, and educational staff. Data analysis followed the interactive model by Miles and Huberman. The findings reveal that the implementation of Islamic-based performance management has integrated values such as amanah (trustworthiness), ihsan (excellence), and tawakkal (reliance on God) into the daily work culture, driven by exemplary leadership, a religious organizational culture, and routine spiritual development programs. This contributes to improved educational quality, teacher discipline, and a conducive religious atmosphere. However, challenges include a lack of collective consistency in value internalization, a high administrative workload that can shift focus from quality, and the absence of explicit integration of spiritual values in formal evaluation and reward systems. The study suggests developing performance indicators based on Islamic values and a holistic reward system for optimal implementation.